Th17 cell-derived IL-17A promoted tumor progression via STAT3/NF-κB/Notch1 signaling in non-small cell lung cancer. (2nd November 2018) - Wang, Ruirui; Yang, Li; Zhang, Chaoqi; Wang, Ruijie; Zhang, Zhen; He, Qianyi; Chen, Xinfeng; Zhang, Bin; Qin, Zhihai; Wang, Liping; Zhang, Yi
ABSTRACT: Non-small cell lung cancer (NSCLC) accounts for the majority of all lung cancer cases, which is the leading cause of cancer deaths worldwide. IL-17░A, the major effector cytokine derived from Th17 cells, is a key cytokine in tumor pathogenesis and modulates tumor progression. We aimed to identify whether IL-17░A derived from Th17 cells promotes the progression of NSCLC. Here we found that the level of Th17 cells was increased in NSCLC and IL-17░A was mainly produced by CD4 + cells (Th17 cells) in NSCLC. IL-17░A enhanced the migration, invasion and stemness of NSCLC via STAT3/NF-κB/Notch1 signaling. Blockade of this signaling inhibited the migration, invasion and stemness of NSCLC mediated by IL-17░A. Th17 cells in NSCLC were closely associated with poor prognosis of NSCLC patients. Our results indicated that Th17 cell-derived IL-17░A plays an important role in tumor progression of NSCLC via STAT3/NF-κB/Notch1 signaling. Therefore, therapeutic strategies against this pathway would be valuable to be developed for NSCLC treatment.